Role of azaamino acid residue in beta-turn formation and stalbility in designed peptide - Lee, HJ; Ahn, IA; Ro, S; Choi, KH; Choi, YS; Lee, KB (MUNKSGAARD INT PUBL LTD, 2000)
The structural perturbation induced by (CH)-H-alpha-->N-alpha exchange in azaamino acid-containing peptides was predicted by ab initio calculation of the 6-31G* and 3-21G* levels. The global energy-minimum conformations for model compounds, For-asaXaa-NH2 (Xaa=Gly, Ala, Leu) appeared to be the beta-turn motif with a dihedral angle of phi=+/-90 degrees, psi=0 degrees. This suggests that incorporation of the azaXaa residue into the i+2 position of designed peptides could stabilize the beta-turn structure. The model azaLeu-containing peptide, Boc-Phe-azaLeu-Ala-OMe, which is predicted to adopt a beta-turn conformation was designed and synthesized in order to experimentally elucidate the role of the azaamino acid residue. Its structural preference in organic solvents was investigated using H-1 NMR, molecular modelling and IR spectroscopy. The temperature coefficients of amide protons, the characteristic NOE patterns, the restrained molecular dynamics simulation and IR spectroscopy defined the dihedral angles [(phi(i+1), psi(i+1)) (phi(i+2), psi(i+2))] of the Phe-azaLeu fragment in the model peptide, Boc-Phe-azaLeu-Ala-OMe, as [(-59 degrees, 127 degrees) (107 degrees, -4 degrees)]. This solution conformation supports a pit-turn structural preference in azaLeu-containing peptides as predicted by the quantum chemical calculation. Therefore, intercalation of the azaamino acid residue into the i+2 position in synthetic peptides is expected to provide a stable beta-turn formation, and this could be utilized in the design of new peptidomimetics adopting a beta-turn scaffold.
Keywords: ASPARAGINE-CONTAINING PEPTIDES; NUCLEAR-MAGNETIC-RESONANCE; SECONDARY STRUCTURE; COUPLING-CONSTANTS; DISTANCE GEOMETRY; AZA-PEPTIDES; ALANINE; PROTEIN; HAIRPIN; SPECTROSCOPY